Comparison of dynamic flat‐panel detector‐based chest radiography with nuclear medicine ventilation‐perfusion imaging for the evaluation of pulmonary function: A clinical validation study. Issue 10 (5th August 2020) - Tanaka, Rie; Matsumoto, Isao; Tamura, Masaya; Takata, Munehisa; Kasahara, Kazuo; Ohkura, Noriyuki; Inoue, Dai; Matsuura, Yukihiro
Abstract : Purpose: Dynamic chest radiography (DCR) is a flat‐panel detector (FPD)‐based functional lung imaging technique capable of measuring temporal changes in radiographic lung density due to ventilation and perfusion. The aim of this study was to determine the diagnostic performance of DCR in the evaluation of pulmonary function based on changes in radiographic lung density compared to nuclear medicine lung scans. Methods: This study included 53 patients with pulmonary disease who underwent DCR and nuclear medicine imaging at our institution. Dynamic chest radiography was conducted using a dynamic FPD system to obtain sequential chest radiographs during one breathing cycle. The maximum change in the average pixel value (Δmax ) was measured, and the percentage ofΔmax in each lung region, calculated relative to the sum of all lung regions (Δmax %), was calculated for each factor (ventilation and perfusion). The Δmax % was compared with the accumulation of radioactive agents (radioactive agents%) on ventilation and perfusion scans in each lung and lung region using correlation coefficients and scatter plots. The ratio of ventilation to perfusion Δmax % was calculated and compared with nuclear medicine ventilation‐perfusion (V/Q) findings in terms of sensitivity and specificity for V/Q mismatch in each lung region. Results: There was a high correlation between Δmax % and radioactive agents% for each lung (Ventilation: r = 0.81, perfusion: r = 0.87). However, correlation coefficients were lower (0.37 to 0.80) when comparing individual lung regions, with the upper lung regions showing the lowest correlation coefficients. The sensitivity and specificity of DCR for V/Q mismatch were 63.3% (19/30) and 60.1% (173/288), respectively. Motion artifacts occasionally increased Δmax %, resulting in false negatives. Conclusions: Ventilation and perfusion Δmax % correlated reasonably with radioactive agents% on ventilation and perfusion scans. Although the regional correlations were lower and the detection performance for V/Q mismatch was not enough for clinical use at the moment, these results suggest the potential for DCR to be used as a functional imaging modality that can be performed without the use of radioactive contrast agents. Further technical improvement is required for the implementation of DCR‐based V/Q studies.